2017
DOI: 10.1155/2017/2869458
|View full text |Cite
|
Sign up to set email alerts
|

Enteric Fever Caused bySalmonella entericaSerovars with Reduced Susceptibility of Fluoroquinolones at a Community Based Teaching Hospital of Nepal

Abstract: Enteric fever continues to be an important public health problem especially in developing countries of the tropical region including Nepal. In this study, we aimed to investigate the incidence of enteric fever associated with Salmonella enterica and determine its antimicrobial susceptibilities to therapeutic antimicrobials in a community based teaching hospital of Nepal. A total of 2,304 blood samples from suspected enteric fever patients attending Manmohan Memorial Teaching Hospital were processed with standa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
32
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 33 publications
(42 citation statements)
references
References 35 publications
9
32
1
Order By: Relevance
“…It acts as an inhibitor of protein synthesis and results in a clinical cure rate of 90% with fever clearance time of 5–7 days in typhoid fever 5457. Our results in terms of sensitivity to ceftriaxone, cefixime, and azithromycin were analogous to the previous literature where Salmonella isolates showed 100% sensitivity against ceftriaxone27 and cefixime,58 and 96.3–100% sensitivity to azithromycin 58,59. A battery of studies had also reported azithromycin to be similar or superior to chloramphenicol, fluoroquinolones, extended spectrum cephalosporins in the management of uncomplicated enteric fever with prompt resolution of clinical symptoms and poor relapse rate 60–66.…”
Section: Discussionsupporting
confidence: 86%
“…It acts as an inhibitor of protein synthesis and results in a clinical cure rate of 90% with fever clearance time of 5–7 days in typhoid fever 5457. Our results in terms of sensitivity to ceftriaxone, cefixime, and azithromycin were analogous to the previous literature where Salmonella isolates showed 100% sensitivity against ceftriaxone27 and cefixime,58 and 96.3–100% sensitivity to azithromycin 58,59. A battery of studies had also reported azithromycin to be similar or superior to chloramphenicol, fluoroquinolones, extended spectrum cephalosporins in the management of uncomplicated enteric fever with prompt resolution of clinical symptoms and poor relapse rate 60–66.…”
Section: Discussionsupporting
confidence: 86%
“…Fluoroquinolone non-susceptibility in S . Typhi started rising in 2002 and reached 96.5% globally in 2015 [ 15 , 27 ]. Fluoroquinolones are not only extensively prescribed for humans but are widespread in animal husbandry.…”
Section: Discussionmentioning
confidence: 99%
“…Increased use of quinolones, such as levofloxacin, at an early age is related to poor susceptibility to garenoxacin [50], a quinolone frequently prescribed in children [51], multiple concurrent antibiotic prescriptions, and lack of education regarding usage were reported in Nepal [52]. The high prevalence of Salmonella enterica infection [53] increased the tendency for physicians to prescribe quinolones for gastroenteritis patients, even though it is actually virus related [51], and increased the quinolone resistance rate [54]. Tuberculosis is prevalent in South Asia, and a quinolone regimen, such as gatifloxacin, is also important for short-course treatment of multi-drug–resistant tuberculosis [55].…”
Section: Discussionmentioning
confidence: 99%